Structural, Electrical, and Optical Properties of Single-Walled Carbon Nanotubes Synthesized through Floating Catalyst Chemical Vapor Deposition - Melorina Dolafi Rezaee; Biplav Dahal; John Watt; Mahir Abrar; Deidra R. Hodges; Wenzhi Li (Nanomaterials, 2024)
Single-walled carbon nanotube (SWCNT) thin films were synthesized by using a floating catalyst chemical vapor deposition (FCCVD) method with a low flow rate (200 sccm) of mixed gases (Ar and H2). SWCNT thin films with different thicknesses can be prepared by controlling the collection time of the SWCNTs on membrane filters. Transmission electron microscopy (TEM) showed that the SWCNTs formed bundles and that they had an average diameter of 1.46 nm. The Raman spectra of the SWCNT films suggested that the synthesized SWCNTs were very well crystallized. Although the electrical properties of SWCNTs have been widely studied so far, the Hall effect of SWCNTs has not been fully studied to explore the electrical characteristics of SWCNT thin films. In this research, Hall effect measurements have been performed to investigate the important electrical characteristics of SWCNTs, such as their carrier mobility, carrier density, Hall coefficient, conductivity, and sheet resistance. The samples with transmittance between 95 and 43% showed a high carrier density of 1021–1023 cm−3. The SWCNTs were also treated using Brønsted acids (HCl, HNO3, H2SO4) to enhance their electrical properties. After the acid treatments, the samples maintained their p-type nature. The carrier mobility and conductivity increased, and the sheet resistance decreased for all treated samples. The highest mobility of 1.5 cm2/Vs was obtained with the sulfuric acid treatment at 80 °C, while the highest conductivity (30,720 S/m) and lowest sheet resistance (43 ohm/square) were achieved with the nitric acid treatment at room temperature. Different functional groups were identified in our synthesized SWCNTs before and after the acid treatments using Fourier-Transform Infrared Spectroscopy (FTIR).